Surface effects on electrical and magnetic properties of Ni75.2Mn23.6Pt1.2 alloy films - Öner, Y. (Elsevier BV, 2016)
Abstract We report on the magnetic, electrical resistivity and ferromagnetic resonance (FMR) properties of polycrystalline thin films of Ni 75.2 Mn 23.6 Pt 1.2 prepared by electron beam evaporation with thicknesses from 10 to 800 nm. We measured field cooled magnetization as a function of temperature as well as hysteresis loops in parallel and perpendicular geometries (field parallel/perpendicular to film surface) at selected temperatures. We observe asymmetric double–shifted hysteresis loops below the freezing temperature, T f, which can be attributed to the competition of unidirectional and uni-axial anisotropy fields. At low temperatures below T f , the main contribution to the temperature dependence of the resistivity is the scattering of conduction electrons by spin-waves, while in the intermediate temperature range between T f and the Curie temperature, T c , the resistivity has a logarithmic temperature dependence due to electron-spin fluctuation scattering. At high temperatures, the most important contribution arises from the electron-phonon scattering mechanism. Finally, FMR measurements were used to probe the magnetic state. We considered the simplest form of the Hamiltonian and used a model based on the Landau-Lifshitz equation. By a rigorous analysis of the angle dependence of the FMR measured at several temperatures, we determined the values of the bulk and surface anisotropy constants, and the exchange stiffness constant. The fitting parameters show that the magnetic ordering is modified significantly by film thicknesses due to the surface anisotropy fields.